Occurrence of zearalenone in corn meal commercialized in south region of Brazil and daily intake estimates in the Brazilian population. Issue 5 (24th June 2019) - Pante, Giseli C.; Silva, Milena V.; Romoli, Jéssica C. Z.; Rocha, Gustavo H. O.; Bando, Erika; Nerilo, Samuel B.; Mossini, Simone A. G.; Machinski, Miguel
Abstract: The purpose of this study was to assess the risk of zearalenone (ZEA) in corn meal produced and commercialized in State of Parana, Brazil. The extraction method carried out with a Romer Mycosep 226 column was found to be efficient due to addition of both diatomaceous earth and centrifuging during the cleaning step. From the total of 84 analyzed samples, 78.6% ( n = 66) were found to be contaminated ZEA at levels between 15.4 and 72.1 μg/kg. This study was the first report on occurrence of positive samples for ZEA in corn meal commercialized in Parana since 2005. The estimated daily intake (EDI) of ZEA for the Brazilian population and for the State of Parana was 3.1 and 2.2 ng/kg bw/day, respectively. The EDI was below the tolerable daily intake of 250 ng/kg bw/day. Despite the low health risk of the population, it was observed that the occurrence of ZEA in corn meal was frequent, which demonstrates the importance of monitoring studies to ensure consumer's health. Practical applications: Occurrence of zearalenone in corn meal was high (78.6%) in Brazil. First report on corn meal samples positive for zearalenone in Paraná, Brazil. No sample exceeded the tolerated limit by both Brazilian and European legislation. EDI due to corn meal consumption was inferior to TDI.